microRNA function in stem cells - Ruohola-Baker, Hannele (Henry Stewart Talks, 2008)
microRNAs, Stem cells, Stem cell cell cycle, Stem cell checkpoints, p21, hESCs, Stem cell self-renewing division, Notch, Niche
Archived at 2021/02/25